Multiculturalism and Compassion: Responding to Mental Health Needs Among Refugees and Asylum Seekers; Comment on "A Crisis of Humanitarianism: Refugees at the Gates of Europe" - Emily Satinsky; Theodoros A. Filippou; Antonis A. Kousoulis (Kerman University of Medical Sciences, 2019)
As Fotaki (2019) argues, the current political climate in Europe is threatening principles of humanitarianism, particularly among refugees and asylum seekers. This commentary builds on that argument, with a spotlight on mental health and culturally relevant service design. By addressing some of the barriers faced by refugees and asylum seekers in accessing mental healthcare, we can address inequalities and develop compassionate societies.